2020
DOI: 10.1101/2020.10.05.327429
|View full text |Cite
Preprint
|
Sign up to set email alerts
|

The landscape of metabolic pathway dependencies in cancer cell lines

Abstract: The metabolic reprogramming of cancer cells creates metabolic vulnerabilities that can be therapeutically targeted. However, our understanding of metabolic dependencies and the pathway crosstalk that creates these vulnerabilities in cancer cells remains incomplete. Here, by integrating gene expression data with genetic loss-of-function and pharmacological screening data from hundreds of cancer cell lines, we identified metabolic vulnerabilities at the level of pathways rather than individual genes. This approa… Show more

Help me understand this report
View published versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

0
3
0

Year Published

2022
2022
2023
2023

Publication Types

Select...
2
1

Relationship

1
2

Authors

Journals

citations
Cited by 3 publications
(3 citation statements)
references
References 58 publications
0
3
0
Order By: Relevance
“…Plasma metabolomic profiling provides a snapshot of metabolic changes [35], which are a good choice for the investigation on diseases and responses to treatment [36]. We identified 3 metabolic pathways that were significantly altered by HDMTX.…”
Section: Discussionmentioning
confidence: 99%
“…Plasma metabolomic profiling provides a snapshot of metabolic changes [35], which are a good choice for the investigation on diseases and responses to treatment [36]. We identified 3 metabolic pathways that were significantly altered by HDMTX.…”
Section: Discussionmentioning
confidence: 99%
“…This is primarily due to the mounting body of evidence highlighting the aberrant metabolic pro les present in tumors. Such dysregulated metabolism not only fuels tumor cell proliferation, recurrence, and metastasis, but also exerts in uence over the immunosuppressive attributes and malignant characteristics of tumors [27][28][29] . As metabolomics research continues to advance, an increasing number of studies have underscored the value of identifying metabolic alterations in patients as a means for early screening across various malignancies, including colon cancer [30][31][32] .…”
Section: Discussionmentioning
confidence: 99%
“…Another question left unanswered is how media composition might impact drug target identification by metabolomics. In mammalian cells, media composition can significantly affect the response to drugs and genetic perturbations (Joly et al , 2021). As such, would the authors have found different results if their yeast had been cultured in a different media?…”
Section: Figure Drug Target Identification By High‐throughput Metabol...mentioning
confidence: 99%